Webinar: A Strategy to Enhance Speaking Skill of Non-native English Speakers - Budiana, Kartika Marta; Yutanto , Hariadi (JEES (Journal of English Educators Society), 2020)
Low competence in speaking for the students of Non-native English speakers has been crucial challenge so far for the teachers in language teaching in Indonesia. This study attempts to explore the effect of webinar applied in teaching speaking on Students of Non-native English Speakers at one of Business schools in Surabaya. There are three classes observed in this study. Before the webinar was applied, the groups were given test to check their proficiency. After conducting the webinar class, the post-test was given to the groups. The instruments to get the data was the oral test. The results reveal that there is an improvement on post test score in the two out of three classes observed. In contrary, the last class has no improvement on their post test score. Moreover, barriers found during the implementation of webinar in speaking class will be explored. HIGHLIGHTS: There is an improvement on the speaking score with webinar using on the two from three classes observed. Practically, the findings of this study are likely able to give positive contribution and technology using experience to all English teachers as well as the students.